Can the Subaltern Think? The Decolonial Turn in Communication Research in Africa - Moyo, Last; Mutsvairo, Bruce (Palgrave Macmillan, 2021)
The title of this chapter is provocative. This is because all scholars, regardless of background, always consider themselves critical thinkers. After all, academic research is by default a space for the robust exchange of ideas and the production of knowledge. At its best, media and communication studies research must be original, critical, transformative, and clearly add to the contours of a multicultural critical theory as imagined in various places and philosophical traditions. Good research must give birth to critical thinking that not only interprets the world, but changes it by unmasking all forms of domination beyond the insubstantial nature of neoliberal theory and Marxian reductionism. In the broader field of the Humanities, theory that both undergirds research and is also produced by research must be critical. As a form of higher order thinking, theory must deliver substantive rationality as opposed to instrumental rationality. In communication studies research, theory must not limit itself to craft skills needed by journalists in industry, but must also seek to produce interventions that align media work with the broader struggle for social justice, egalitarianism, and freedom of the self and community.